Aerotropoli agriculture: a study of the Dube AgriZone at the Dube TradePort, KwaZulu-Natal - Cassim, Adila (Department of Environmental and Geographical Science, 2015)
The Dube AgriZone has been described as an agricultural cluster development zone situated at an air logistics platform called the Dube TradePort in La Mercy, KwaZulu-Natal. The Dube AgriZone was launched in 2012 and aims to stimulate the growth of KwaZulu-Natal's perishable goods sector by producing high-value fresh produce all-year round in high quantities for both domestic and international markets. The main objective of this study was to investigate the current performance status of the Dube AgriZone's operation. This research made use of data collected from key informant interviews, document analysis and observational recordings during site visits. The information was used to compile a case study of the Dube AgriZone as an example of agriculture at an airport precinct (aerotropoli agriculture). Findings of this research have shown that the Dube AgriZone has operated with some success and failure during Phase 1. Infrastructural, logistics, financial, market, climate and administrative issues at the farming facility surfaced during this investigation. This study advocates that more research is needed on how to assist the Dube AgriZone project to operate optimally combating the current issues that it faces. It is hoped that this research can offer an interesting contribution to information on agricultural projects situated at airport precincts.